Time remaining:
Please find A, B, and C. Thanks!!

label Mathematics
account_circle Unassigned
schedule 0 Hours
account_balance_wallet $5

Oct 17th, 2017

a) For f(g) just replace x in f = 3x-12 by x/3+4, thus 

f(g(x)) = 3((x/3)+4) -12 = x 

b) similarly g(f(x)) = 1/3(3x-12)+4 = x.  

c) From a and b,  f(g(x)) = g(f(x)) = x, and they have the same domain of R,  so g(x) = f^-1(x) and f= g^-1(x) we see that function f and g are inverses of each other.  

 

Apr 5th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Oct 17th, 2017
...
Oct 17th, 2017
Oct 18th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer